Legitimating a religion through culture: revisiting Peter Clarke's discussion on the globalisation of Japanese new religions. Issue 1 (2nd January 2021) - Kato, Masato
ABSTRACT: Peter Clarke's work on the globalisation of Japanese new religions in the West remains a primary point of reference in this field. Despite its ground-breaking contribution, there needs to be a re-evaluation of his conclusion, which considers Japanese cultural elements of these religious groups as a hindrance to local adaptation in the West. This article revisits his claim by strategically focusing on a religious group known as Tenrikyō, which has been described by Clarke as a primary example of unsuccessful Japanese new religions in the West due to its strong association with Japanese traditional culture. This study highlights the group's approach to use Japanese culture as a resource for increasing its public visibility and legitimacy in France, an initiative which coincided with a period of growing interest in the Japanese language and popular culture as well as the cult controversy in the country. By analysing the promotion of Japanese culture as a non-religious strategy of legitimation, if not competition, this study argues that the implications of particular cultural elements associated with a religious group need to be assessed in the light of the social dynamics of legitimation and delegitimation in a given context.